ON PRESENTATIONS OF THE GROUP 7.7 FROM KOUROV NOTEBOOK - Shirvanyan, N. V.; Shirvanyan, V. L. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2005)
In the well-known book [1] unsolvable problems there is one special group presented by two generators and the defining relations. In this paper we give simple presentations of the group.
Keywords: Kourov Notebook; two generators; simple presentations